Translating words into actions: are governments acting on the advice of the World health report? - David C McCoy
Every year, WHO produces the World health report: the 2005 report concentrated on maternal, neonatal and child health. But what is the value of these reports? Are they ritualistic publications designed to promote WHO, or are they worthy of proper discussion and debate? One would think that given the current crises in global health, the annual report of the UN's primary agency for health would be important. However, unless there is evidence that these reports are taken seriously, discussed and debated, and shown to have an effect, a conclusion might be drawn that they are largely insignificant. And that would consign WHO to a level of insignificance that it does not warrant. In this discussion of the 2005 report, I aim to provoke a response from both WHO and the international health community to demonstrate that the annual World health reports are meaningful. Furthermore, I suggest here that WHO shows its commitment to the recommendations of the 2005 report by monitoring how well recommendations have been taken forward.